Solcellsanläggning vid LTU - Fogelström, Frej; Rosendal, Andreas (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2021)
In this project, intended photovoltaic installations on the campus area of Luleå University of Technology are cost–estimated, designed and mapped based on solar power in northern conditions. An increased precipitation of snow and low solar angles are the main factors influencing the energy yield from PV installations in northern conditions. The reduced irradiation during winter results in a power production corresponding to only a few percent of the production during summer. Snow shading can lead to a 30% annual production loss and is strongly correlated to module tilt and placement. The roof surfaces selected for the installations have shown good potential regarding yearly irradiation based on modeling, simulations, solar mapping and photography. The modules selected in the project are monocrystalline moduls in half–cell design from Trina Solar, Longi Solar and Q–cells. Placement has been made in a landscape position with southern orientation. Simulated production for the A–house installation was 260 MWh, B–house 200 MWh, C–house 190 MWh, E–house 310 MWh, F–house 450 MWh and Polstjärnan 80 MWh. Total annual production for the campus has been calculated to approximately 1,5 GWh. The total cost for the installation of each building was estimated for the A–building 1,4 MSEK; B– and C– building 1,1 MSEK; building 1,7 MSEK; building 2,4 MSEK and Polstjärnan 0,4 MSEK. The total cost for all the installations was estimated to 8,1 MSEK with a payback time estimated at 10 years. The most feasible case in terms of produced solar power in relation to total investment cost is the modules from Q–cells. The priority order for the construction of each installations in descending order is: A–house, F–house, E–house, C–house, B–house and Polstjärnan based on availability and profitability. Simulated production in relation to the buildings’ electricity demand shows that storage and feedback to the electricity grid is not relevant for the roof–mounted installations in the project. To cover the electricity demand with ...